TRANSFORMATION OF ISLAMIC BOARDING SCHOOL EDUCATION IN THE DIGITAL ERA: A CRITICAL ANALYSIS OF THE INTERNALIZATION OF QUR'ANIC VALUES - Muchamad Suradji; Faridi Faridi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the transformation of Islamic boarding school education in the digital era with a focus on the internalization of Qur'anic values as the core of Islamic education. The rapidly growing digitalization phenomenon has brought opportunities and challenges for Islamic boarding schools, both in terms of management, learning methods, and the transmission of religious values. The method used is library research with a descriptive qualitative approach, through a critical review of reputable journals, academic books, and relevant documents discussing the digitalization of Islamic education and the practice of internalizing Qur'anic values. The results show that digitalization not only affects the technical aspects of the implementation of Islamic boarding school education, but also impacts the pattern of teacher-student relationships, the authority of kiai, and the depth of internalization of Qur'anic values. On the one hand, digital technology expands access to knowledge, enriches learning methods, and increases the effectiveness of Islamic boarding school management. However, on the other hand, there is a risk of reducing the meaning of Qur'anic values, spiritual degradation, and the penetration of external cultures that are not always in line with Islamic boarding school traditions. This research emphasizes that the integration of digital technology and the internalization of Quranic values must be carried out critically and selectively, while still upholding the role of the exemplary role of Islamic scholars (kyai). The academic contribution of this research lies in the presentation of a new conceptual framework that connects digital transformation with the internalization of Quranic values, thus serving as a reference in developing adaptive, authentic, and transformative Islamic education strategies.